Excel 2010 for Engineering Statistics A Guide to Solving Practical Problems - Quirk, Thomas J. (Springer International Publishing : Imprint: Springer, 2014)
This is the first book to show the capabilities of Microsoft Excel to teach engineering statistics effectively.  It is a step-by-step exercise-driven guide for students and practitioners who need to master Excel to solve practical engineering problems.  If understanding statistics isn't your strongest suit, you are not especially mathematically-inclined, or if you are wary of computers, this is the right book for you.  Excel, a widely available computer program for students and managers, is also an effective teaching and learning tool for quantitative analyses in engineering courses.  Its powerful computational ability and graphical functions make learning statistics much easier than in years past.  However, Excel 2010 for Engineering Statistics: A Guide to Solving Practical Problems is the first book to capitalize on these improvements by teaching students and managers how to apply Excel to statistical techniques necessary in their courses and work.                                                Each chapter explains statistical formulas and directs the reader to use Excel commands to solve specific, easy-to-understand engineering problems.  Practice problems are provided at the end of each chapter with their solutions in an Appendix.  Separately, there is a full Practice Test (with answers in an Appendix) that allows readers to test what they have learned.   Includes 159 Illustrations in color Suitable for upper undergraduates or graduate students At the beginning of his academic career, Prof. Quirk spent six years in educational research at The American Institutes for Research and Educational Testing Service.  He then taught Social Psychology, Educational Psychology, General Psychology, Marketing, Management, and Accounting at Principia College, and is currently a Professor of Marketing in the George Herbert Walker School of Business & Technology at Webster University based in St. Louis, Missouri (USA) where he teaches Marketing Statistics, Marketing Research, and Pricing Strategies.  He has written 60+ textbook supplements in Marketing and Management, published 20+ articles in professional journals, and presented 20+ papers at professional meetings.  He holds a B.S. in Mathematics from John Carroll University, both an M.A. in Education and a Ph.D. in Educational Psychology from Stanford University, and an M.B.A. from The University of Missouri-St. Louis.